Fault tolerant, energy efficient and secure clustering scheme for mobile machine‐to‐machine communications. Issue 10 (19th February 2014) - Karim, Lutful; Anpalagan, Alagan; Nasser, Nidal; Almhana, Jalal; Woungang, Isaac
ABSTRACT Designing energy efficient, fault tolerant and secure clustering scheme is important for machine‐to‐machine (M2M) communications that comprise a large number of sensors. Existing works on M2M communications include designing M2M layered architecture, device model, Quality of Service (QoS) categorisation of M2M services and potential M2M applications. However, designing secure and fault tolerant clustering schemes has not received much attention in M2M research. Thus, this paper introduces a fault tolerant, energy efficient and secure clustering scheme for M2M (FESM) area networks that minimises the number of cluster heads (CHs) and active nodes to reduce network energy consumption. The machine type communication gateway and CHs transmit beacon messages to discover the failure of CHs and member nodes, respectively. The security mechanism is lightweight but efficient. It uses simple permutation‐based shared keys between (i) member nodes and CHs; (ii) gateway nodes and CHs; and (iii) CHs and machine type communication gateway. Experimental results demonstrate that the FESM clustering scheme reduces network energy consumption and increases network lifetime as compared with the existing Fault Tolerant and Energy Efficient Clustering Protocol (FTEEC), Dynamic Static Clustering Protocol (DSC) and Low Energy Adaptive Clustering Hierarchy (LEACH) protocols. We also analyse the security mechanism of the FESM protocol and find that it is very effective against well‐known attacks such as sybil, wormhole and black hole. Copyright © 2014 John Wiley & Sons, Ltd.